Participatory Mapping of Environment Sanitation Conditions in Settlement of Floating House in Ternate City - Firdawaty Marasabessy; Vrita Tri Aryuni (Aceh International Journal of Science and Technology, 2020)
The water settlement has unique and distinctive characteristics, but it can become an environmental problem if the sanitary conditions are poor. The poor sanitary occurred in the water settlement, namely in Makassar Timur and Mangga Dua Utara, which were initially iconic settlements, but now, both of these settlements have environmental degradation. In line with the Sustainable Development Goals, strengthening community participation was carried out to realize clean water and proper sanitation. The research aimed to map the environmental sanitary conditions by involving community participation. This mapping describes sanitary water settlement characteristics to become a planning database to handle both areas' sustainable hygienic. The results showed that the sanitary achievement index in the two regions, above 50% of the conditions were carried or sufficient. The findings showed the mapping of settlement on the water in the two areas, revealed environment condition with the same characteristics in which the environmental conditions had experienced environmental degradation due to contamination of water bodies because of solid and liquid waste originating from residential houses deliverables from upland settlements. In the future, the settlement environment in Makassar Timur District will be planned to be completely stockpiled. As a result, this environmental area will lose its identity as a settlement on the water. Meanwhile, land conflicts occurred in Mangga Dua Utara District's settlement, resulting in the lack of government programs in this environment to structure slum environmental conditions